2022
DOI: 10.2147/dddt.s367277
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide-Releasing Molecule-3 Enhances Osteogenic Differentiation of Rat Bone Marrow Mesenchymal Stem Cells via miR-195-5p/Wnt3a Pathway

Abstract: Purpose Bone marrow-derived mesenchymal stem cells (BMSCs) are hopeful in promoting bone regeneration as their pluripotency in differentiation. Our previous study showed that carbon monoxide-releasing molecule-3 (CORM-3) increased the osteogenic differentiation of rat BMSCs in vitro. However, the mechanism remained unclear. MicroRNAs (miRNAs) play a very important role in modulating the osteogenic differentiation of BMSCs. Therefore, we researched the miRNAs involved in CORM-3-stimulated osteogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Comparisons between the control and model group cells during the period of osteogenic induction by β-GP revealed increases in the expression of miR-195-5p, Wnt3a, and β-catenin over time and a corresponding reduction in the expression of Smad7. The findings of a recent study have similarly indicated that carbon monoxide-releasing molecule 3 promotes osteogenic differentiation of rat BMSCs via miR-195-5p/Wnt3a [ 28 ], whereas other studies have confirmed that miR-195-5p enhances the osteogenic differentiation of cells and is associated with Smad7 [ 29 , 30 ]. These findings accordingly persuaded us to focus our research on the effects of miR-195-5p and Smad7 on the osteogenic differentiation of VSMCs and the Wnt/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons between the control and model group cells during the period of osteogenic induction by β-GP revealed increases in the expression of miR-195-5p, Wnt3a, and β-catenin over time and a corresponding reduction in the expression of Smad7. The findings of a recent study have similarly indicated that carbon monoxide-releasing molecule 3 promotes osteogenic differentiation of rat BMSCs via miR-195-5p/Wnt3a [ 28 ], whereas other studies have confirmed that miR-195-5p enhances the osteogenic differentiation of cells and is associated with Smad7 [ 29 , 30 ]. These findings accordingly persuaded us to focus our research on the effects of miR-195-5p and Smad7 on the osteogenic differentiation of VSMCs and the Wnt/β-catenin pathway.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-195-5p has been linked to osteogenic differentiation via Wnt3a. [28,29]. This miRNA has demonstrated anti-inflammatory properties in inflammatory models such as atherosclerosis [30], while it has also been shown to have pro-inflammatory effects in osteoarthritis [31] and ulcerative colitis [32], whereas hsa-miR-146a-5p may promote differentiation in dental stem cells by targeting Traf6 via the NF-κB signaling pathway [33].…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup of participants with diagnosed RA was formed from patients undergoing rheumatological treatment at the VU Hospital Santaros Clinics. In total, 91 participants diagnosed with RA, who met the ACR/EULAR 2010 rheumatoid arthritis classification criteria, were enrolled in the study and were referred for periodontal status evaluation [29]. A single, qualified researcher rheumatologist (E.P.)…”
Section: Study Population and Clinical Examinationmentioning
confidence: 99%